KAJIAN RELEVANSI DELIK ADUAN PADA IMPLEMENTASI UNDANG-UNDANG HAK CIPTA - Fitri Pratiwi Rasyid (Fakultas Hukum Universitas Gadjah Mada, 2020)
AbstractLaw enforcement efforts against copyright infringement in Indonesia are regulated as a complaint offense under Article 120 of Law Number 28 of 2014 concerning Copyright. Complaint offense implementation had connected with one consideration suggested that the officials having difficulty to distinguish between an original work and a copy. Referring to normative study that has been conducted, the complaint offense is irrelevant since it restricts law enforcement capacity of providing copyright protection. Appropriately, to protect creators and/or copyright holders whose rights have been violated, the officials should take an action without waiting for a complaint about the presence of copyright infringement.IntisariUpaya penegakan hukum terhadap pelanggaran hak cipta di Indonesia diatur sebagai delik aduan berdasarkan Pasal 120 Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta. Delik aduan berlaku dengan salah satu pertimbangan bahwa aparat penegak hukum kerap sulit membedakan ciptaan yang asli dengan tiruannya. Bersumber pada pengkajian normatif yang telah dilakukan, delik aduan tidak relevan diterapkan karena membatasi ruang gerak penegakan hukum dalam memberikan pelindungan hukum untuk berkarya. Sepatutnya, untuk melindungi pencipta dan/atau pemegang hak cipta yang dilanggar haknya, aparat penegak hukum dapat bertindak tanpa harus menunggu aduan pada pelanggaran hak cipta yang terjadi.